Senior High School Students' Knowledge of The Role of Mathematics in The Development of Science and Technology - Amelia, Rika; Hidayana, Rizki Apriva; Syarifudin, Abdul Gazir; Megantara, Tubagus Robbi; Chairunnisa, Nadine Zahra; Manuela, Angellyca Leoni; Kholipah, Nenden Siti Nur (Research Collaboration Community (RCC), 2025)
Mathematics plays a significant role in developing science and technology (also known as IPTEK in Indonesian). However, students' understanding of the contribution of mathematics to the progress of IPTEK still needs to be improved. This study examines the knowledge of senior high school students (also known as SMA in Indonesian) regarding the role of mathematics in developing IPTEK. The method used is a quantitative survey, and questionnaires were distributed to SMA PGRI Cicalengka students. The data obtained were analyzed to determine the level of students' understanding of the relationship between mathematics and its applications in various fields of science, such as physics, biology, and technology. The study results showed that although most students understand mathematics is important in IPTEK, most still need to learn its specific applications in modern technology and scientific innovation. This study suggests the need for more contextual and applicable learning about the role of mathematics in the development of IPTEK so that students can better appreciate and understand the contribution of mathematics in everyday life.